Work and AI 2030 Challenges and Strategies for Tomorrow's Work - Knappertsbusch, Inka.; Gondlach, Kai. (Wiesbaden : Springer Fachmedien Wiesbaden : Imprint: Springer, 2023)
In ten years, working with artificial intelligence (AI) will be just as much a part of our everyday lives as using a cell phone is today. 78 recognized experts from the worlds of practice and research provide deep insights and outlooks regarding the influence of AI on everyday working life in 2030, explaining with practical tips how you can prepare for this development. The 41 concise articles cover a broad spectrum in each area examined. Their standardized structure offers a summary of the status quo, concrete examples, future expectations, an overview of challenges and possible solutions, and practical tips. The volume begins with societal and ethical issues before discussing legal considerations for employers and HR professionals, as well as those working in the judicial system. The other chapters examine the impact of AI on the world of work in 2030 in the sectors of business, industry, mobility and logistics, medicine and pharmaceuticals, and (further) education. The editors Inka Knappertsbusch is a lawyer in the area of labor and employment law and employee data protection at the international law firm CMS Germany. She is passionate about hot topics of the future such as the impact of legal tech and artificial intelligence on the employment relationship. Her clients include international corporations as well as medium-sized companies. Kai Gondlach holds a degree in sociology, political/administrative science and futurology. His research centers on three areas in particular: digitalization & AI, working environments & education, and climate & sustainability. The results inspire his keynote lectures, scientific papers, his podcast as well as his own blog.
The specter of German Angst: Are we too skeptical for AI development? -- Practice Guide AI = Collaborative and Interdisciplinary -- Future Collaboration between Humans and Artificial Intelligence -- Innovation and Startups.Artificial Intelligence Demands Corporate Digital Responsibility -- AI Ethics and Neuroethics Advance Relational AI Discourse -- Digital Product Monitoring Obligations for Smart Products -- The Use of AI-Based Speech Analysis in the Job Application Process -- Individual Legal Issues in the Use of AI.AI in the Enterprise: Is the employer liable or the AI as an e-person? -- The works council's right of co-determination under Section 87 (1) No. 6 BetrVG in the use of AI systems in the company -- Data protection law assessment of predictive policing in the employment relationship -- Legal requirements for AI decisions in administration and the judiciary -- Intelligent IT systems in the company -- Successful implementation of AI in the enterprise -- Responsible and robust AI in enterprises -- AI as a driver of hybrid forms of employment -- The future of financial planning in enterprises -- Potentials of AI for production -- The grassroots movement of artificial intelligence -- Employment effects emanating from AI and the changes in work organization -- : Opportunities of AI for work design in the manufacturing industry -- The role of humans in the context of sovereign data spaces.AI in the skilled trades -- Potentials in the field of mobility through mathematical methods of artificial intelligence -- How AI enables business models and gives rise to job profiles -- Industrial AI - Smart Factories and Team Robotic .AI in the automotive industry.AI in the rail sector.AI as an opportunity for the future airline business.AI in intralogistics.Through AI, medicine becomes more efficient, individualized and preventive -- : AI in the clinical treatment pathway -- To make medicine that no human has ever seen before.AI in the healthcare market -- Data-based innovations in the healthcare sector and strategic preparation of renowned global IT companies -- : AI add-on qualification.Educational Technology and AI -- Artificial Intelligence in Continuing Education of the Future.AI in Vocational Rehabilitation - Intelligent Assistance for People with Disabilities.
Keywords: Management; Commercial law; Personnel management; Management; Business Law; Human Resource Management